Endogenous Heparinoids May Cause Bleeding in Mucor Infection and can be Detected by Nonactivated Thromboelastometry and Treated by Recombinant Activated Factor VII: A Case Report. Issue 8 (February 2016) - Durila, Miroslav; Pavlicek, Petr; Hadacova, Ivana; Nahlovsky, Jiri; Janeckova, Daniela
Abstract : Abstract: Mucormycosis is an aggressive fungal infection, which invades endothelial cells of blood vessels. This condition might lead to destruction of endothelium and release of heparin-like substances to the bloodstream and cause life-threatening bleeding, which is not well described in the literature. We present a patient with mucormycosis who experienced life-threatening bleeding, although no standard laboratory test could detect any coagulopathy. The cause of bleeding-coagulopathy was detected only by nonactivated thromboelastometry (NATEM), which revealed the presence of heparin-like substances. After treatment with recombinant activated FVII rotational thromboelastometry, results improved and the patient stopped bleeding. Regular application of the drug was necessary during acute phase of infection to prevent further bleeding. In this case report, we show that NATEM can detect the presence of heparin-like substances in bleeding patient with mucormycosis infection and that recombinant activated FVII can be used to stop and prevent bleeding until infection resolves.